The Influence of Active Learning Strategy with Cardshort Method at SMA 2 Percut Sei Tuan - Ayundari , Sella; Annisa, Annisa; Armiati , Rika (Journal of Biology Learning, 2023)
Active learning is optimizing the use of all the potential possessed by students, so that all students can achieve satisfactory learning outcomes according to their personal characteristics. In this mini-research task, the author discusses active learning strategies using the card short method. The purpose of this study was to determine the effect of active learning strategies using the card short method on student learning outcomes. The method used in this study is the method of direct observation or survey in Class XI IPA 3 SMAN 2 Percut Sei Tuan. Data collection techniques used pretest and posttest and the results showed that there were differences in the effect of active learning strategies using the cardhort method with the blood circulatory system material. The card sort learning method with the technique of the games is expected to help students understand the lesson and understand the classification of the circulatory system material. Based on the results of research conducted at SMA Negeri 2 Percut Sei Tuan, there are differences in the influence of active learning strategies using the cardshort method with blood circulatory system material.